Strategi Konter Gerakan Islam Transnasional melalui Dakwah Struktural - Siti Asiyah; Muh. Luthfi Hakim (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2022)
The majority of the Indonesian population who are Muslim with different understandings of Islam is one of the backgrounds for the emergence of new movements that "deviate" in the name of religion. The Transnational Islamic Movement is one of the new Islamic movements that have emerged in several parts of Indonesia, this movement has spread to the Jepara Regency area. Using the qualitative approach used and methods of documentation, interviews, and observations, this paper will describe the Transnational Islamic movement or organization and how the da'wah strategies were carried out in overcoming and dealing with the movement. The results of this study are the strategies used in an effort to overcome the Transnational Islamic movement through a structural approach and the intervention of various parties, both from the da'wah institutions in Jepara Regency, the Indonesian Ulama Council (MUI), Jepara Police, and Islamic Religious Counselors in Jepara Regency so that the organization or The transnational Islamic group, in this case, the Khilafatul Muslimin Ummul Quro group was successfully disbanded. Mayoritas penduduk Indonesia yang beragama Islam dengan pemahaman Islam yang berbeda menjadi salah satu latar belakang munculnya gerakan-gerakan baru yang “menyimpang” dengan mengatasnamakan agama. Gerakan Islam Transnasional merupakan salah satu gerakan Islam baru yang muncul di berbagai wilayah Indonesia, gerakan ini telah menyebar ke wilayah Kabupaten Jepara. Dengan menggunakan pendekatan kualitatif dan metode dokumentasi, wawancara, dan observasi, tulisan ini akan memaparkan gerakan atau organisasi Islam Transnasional dan bagaimana strategi dakwah yang dilakukan dalam mengatasi dan menghadapi gerakan tersebut. Hasil penelitian ini adalah strategi yang digunakan dalam upaya mengatasi gerakan Islam Transnasional melalui pendekatan struktural dan intervensi oleh berbagai pihak, baik dari lembaga dakwah di Kabupaten Jepara, Majelis Ulama Indonesia (MUI), Polres Jepara , dan Penasihat Agama Islam di Kabupaten Jepara sehingga organisasi atau kelompok Islam transnasional dalam hal ini kelompok Khilafatul Muslimin Ummul Quro berhasil dibubarkan.